EAP practitioner formation in a low-resource EMI context: Developing an in-house EAP continuing professional development (CPD) programme in Lebanon - Angela Hakim (International Journal of English for Academic Purposes)
A growing body of English for Academic Purposes (EAP) literature highlights the need for a focus on the EAP practitioner. One area which warrants further attention is continuing professional development (CPD), which is a key component of EAP practitioner formation. This reflective, practice-based paper provides a brief overview of the literature relevant to EAP practitioner formation before discussing the ongoing needs analysis and development of an in-house CPD programme for EAP practitioners, who are transitioning from teaching English for general academic purposes to teaching English for specific academic (ESAP) purposes and who are implementing a genre-based, discipline-specific approach in credit-bearing ESAP modules. The paper concludes with a discussion of implications for EAP practitioners and CPD in low-resource contexts. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.